Early development of two tropical fishes (Perciformes: Sciaenidae) from the Pantanal of Mato Grosso, Brazil - Leika Taguti, Tatia (2015)
The early life history stages are inadequately known for most fishes of the Neotropical region. Thus, larvae and juveniles of the species Pachyurus bonariensis and Plagioscion ternetzi, two corvina species found in the Pantanal of Mato Grosso, Brazil, were described, assessing ontogenetic changes in their external morphology, pigmentation, fin development, morphometry and meristics. Fish were collected in Chacororé Bay, on the Cuiabá River, between March 2000 and March 2004. Eighty individuals of each species were analyzed, comprising 60 larvae and 20 juveniles. Pachyurus bonariensis larvae exhibited a mouth in a terminal position that became sub-terminal; large, well-pigmented, spherical eyes that became small and elliptical in postflexion; preopercular spines (two internal and four external); 23 to 27 myomeres; initially sparse pigmentation that intensified, mainly in the ventral region; and the following fin formation sequence and total number of spines and rays: caudal, dorsal (XI+29-32), anal (II+six), pelvic (I+five) and pectoral (15-17). In contrast, the larvae of P. ternetzi exhibited a terminal mouth; large, well-pigmented, spherical eyes that decreased in size during development; preopercular spines (three internal and four external); 23 to 26 myomeres; pigmentation that was initially sparse, became evident only in late postflexion stage, with the presence of some chromatophores on the top of the head; and the following fin formation sequence and total number of spines and rays: caudal, dorsal (XI+30-36), anal (II+six), pelvic (I+five) and pectoral (16-18). In relationship the morphometric variables, only the snout-anal fin length differed between the two species, being initially larger in P. ternetzi, whereas it only became larger in juvenile P. bonariensis after 34 mm. Despite the difficulty of intraspecific identification among fish larvae collected in natural environments, the morphological and morphometric tools used in the present study were effective in separating the early stages of development of the two morphologically similar species that share the same environment for reproduction.